Study protocol for Goodform - a classroom-based intervention to enhance body image and prevent doping and supplement use in adolescent boys - Joanna Rachel Doley; Siân Alexandra McLean; Scott Griffiths; Zali Yager (BMC, 2020)
Abstract Background Very few programs aimed at improving body image among adolescent boys have been effective, and there is still no clear evidence as to what will work for universal prevention of eating disorders and body dissatisfaction with this group. We combined two previously efficacious programs and used a design thinking framework to optimise program content alongside potential end-users including adolescent boys, teachers, parents, and experts. Goodform is a four-session universal program that aims to reduce body dissatisfaction and prevent the use of muscle-building supplements among 14-to-16 year old adolescent boys. Methods/design Goodform will be trialled using a cluster randomised controlled trial (RCT) conducted in Australian schools, with Year 9 boys as participants. The intervention is teacher-delivered. Data will be collected at three time points: baseline, post-intervention, and follow-up (2 months). Three primary outcome constructs will be examined, including body dissatisfaction (Male Body Attitudes Scale-Revised) and attitudes towards appearance and performance enhancing substances (APES; Outcome Expectations for Steroid and Supplement Use, Intentions to use APES) and actual use of APES at each time point. Three secondary outcome constructs will be examined, which are social norms for APES (adapted Peer Norms Scale), negative body talk (Male Body Talk Scale), and internalisation of and pressure to attain appearance ideals (Sociocultural Attitudes Towards Appearance Questionnaire-4 Revised). Internalisation of appearance ideals will also be examined as a mediator of change in primary outcomes. Teachers will provide data on adherence to lessons, student engagement/enjoyment, and understanding of the content. Discussion The GoodForm RCT will trial a novel, generalizable, and extensively developed program intended to improve boys' body image and reduce actual and intended APES use. We anticipate that it will provide a novel contribution to the field of boys' body dissatisfaction prevention. Trial registration This trial was retrospectively registered with the Australian and New Zealand Clinical Trials Registry on May 14th 2019, registration number ACTRN12619000725167.